(3GdMeGjI GdbGfhfjI ddeSJgdc ai GdJYGedGJ GdEdcJQhfjI (B/ s - (3VGQi JeQGf GdTeQi s; (3SejMI GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3HQRJ eTcdI GdOQGSI ef NdGd JdeS GdHGMK hGSJTYGQg ddeNGWQ GdJj jecf Gf JUjH GdeLJeY LQGA HYV GdeeGQSGJ GdNGWFg ef bHd GdbGFejf Ydi EOGA GdGfTWI GdJShjbjI aj GZdH GdefXeGJ GdeYfjI HGdNOeGJ hGdJLGQI GdEdcJQhfjI(B: (3hbO JRGjO GgJeGe GdHGMK HPdc fJjLI GMSGSg HJbUjQ Jdc GdefXeGJ fMhMeGjI Mbhb GdeSJgdcjf(B. (3hef Ke Jcef ETcGdjI GdOQGSI aj HjGf GdeTcdGJ GdJj JhGLg GdeSJgdc aj GdJYGbO GdEdcJQhfj(B: (3ShGA aj eQMdI eG bHd GdJYGbO(B: (3Chaj eQMdI EHQGe GdYbO GdEdcJQhfj(B: (3Chaj eQMdI JfajP GdYbO GdEdcJQhfj(B: (3agPg GdOQGSI SJbhe HGdELGHI Ydi GdJSGDdGJ GdJGdjI(B: 1-(3eG gj eHQQGJ MeGjI GdeSJgdc ef GdefXhQ GdJbdjOj hGdJbfj? (B2-(3eG gj Mbhb GdeSJgdc aj cGaI eQGMd GdJYGbO GdEdcJQhfj? (B3-(3cjajI MeGjI GdeSJgdc ai eLGd GdNOeGJ hGdJLGQI GdEdcJQhfjI? s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2017(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B289-297s
Keywords: (3fXGe YdGeI GdLhOIs; (3GdMb ai GdYOhds; (3GdCWQGa GdaGYdI ai MeGjI GdeSJgdcs; (3LeYjGJ MeGjI GdeSJgdc s; (3GdeSJgdc GdEdcJQhfis; (3GdYbO GdEdcJQhfis; (3GdhaGA GdEdcJQhfis; (3LQjeI GdYOhGf Ydi GdEFJeGf GdQbeis; (3eYhbGJ MeGjI GdeSJgdc GdEdcJQhfis; (3GdJhbjY GdEdcJQhfis; (3LQGFe GdeYGedGJ GdEdcJQhfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs